La oposición préterito perfecto simple versus préterito imperfecto: una propuesta cognitivo-prototípica - Funes, María Soledad; Poggio, Anabella Laura (El Colegio de México, 2020)
In accordance with the prototypical-cognitive approach, which postulates that semantics and pragmatics are motivated by syntax, the present study formulates the hypothesis that in the opposition between the Spanish preterit and the imperfect, each verb tense has a cluster of semantic attributes which define them, depending on the context in which they occur and on the speaker’s communicative purpose. These attributes are related not only to the grammatical aspect of the verb but to the discursive function. In order to confirm this hypothesis, the uses of Spanish preterit and imperfect have been analysed qualitatively and quantitatively in a corpus of narrative texts.